KEJADIAN BBLR: APAKAH TERDAPAT KORELASI ASPEK DEMOGRAFI? - Yuni Surya Putri; Sulistiyowati Sulistiyowati; Jihan Alfira (Ensiklopedia of Journal, 2026)
Low birth weight (LBW) is a public health issue that remains a serious concern, especially in developing countries. Based on a review of documents and routine health service reports, the Caile Community Health Center is recorded as one of the health centers with the highest incidence of low birth weight (LBW) in Bulukumba District. Data shows that the number of LBW cases in the Caile Community Health Center working area reached 52 cases, which is relatively high compared to other community health centers in the same area. The purpose of this study was to determine the correlation between demographic aspects and LBW. The research design used in this study was case control. The study was conducted in the Caile Community Health Center working area in July 2025. The population in this study was all mothers who gave birth at the Caile Community Health Center. The research sample consisted of 30 cases and 30 controls. The sampling technique used was purposive sampling. The research instrument used was a research questionnaire. Data analysis was performed using univariate and bivariate methods. The results showed a relationship between gestational age (p value: 0.042) and maternal age (p value: 0.020) and LBW. It is recommended that health workers monitor mothers who experience complications during pregnancy, especially those aged 20 and ≥35 years.   Keywords: Low birth weight, Pregnant women, Pregnancy